2023
DOI: 10.1186/s13244-023-01402-z
|View full text |Cite
|
Sign up to set email alerts
|

CT analysis of thoracolumbar body composition for estimating whole-body composition

Abstract: Background To evaluate the correlation between single- and multi-slice cross-sectional thoracolumbar and whole-body compositions. Methods We retrospectively included patients who underwent whole-body PET–CT scans from January 2016 to December 2019 at multiple institutions. A priori-developed, deep learning-based commercially available 3D U-Net segmentation provided whole-body 3D reference volumes and 2D areas of muscle, visceral fat, and subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The convolutional neural network segmentation model treats each patient's CT image as an array unit, utilizing GPU acceleration to simultaneously process multiple layers of data. In contrast, manual segmentation requires layer-by-layer segmentation, resulting in lower efficiency [30,31]. Unlike traditional 2D convolutional neural networks, the 3D convolutional neural network employed in this study accounts for spatial and contextual information between CT slices.…”
Section: Discussionmentioning
confidence: 99%
“…The convolutional neural network segmentation model treats each patient's CT image as an array unit, utilizing GPU acceleration to simultaneously process multiple layers of data. In contrast, manual segmentation requires layer-by-layer segmentation, resulting in lower efficiency [30,31]. Unlike traditional 2D convolutional neural networks, the 3D convolutional neural network employed in this study accounts for spatial and contextual information between CT slices.…”
Section: Discussionmentioning
confidence: 99%
“…We used this measurement approach instead of using whole-body composition results obtained on chest CT because not all patients had exactly the same CT scan coverage. Indeed, multi-slice averaged body composition analysis results at the level of T12-L1 are known to be well correlated with whole-body composition [ 31 ]. Therefore, in this study, the subcutaneous and visceral fat areas were summed and defined as body fat area to represent whole-body fat.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the studies by Arayne et al [38] and Koitka et al [39] emphasized the consistency and possible clinical application of body composition analysis at different lumbar levels (e. g., T4 and L3). Furthermore, the study of Hong et al [40] further demonstrated the accuracy of CT analysis of the thoracolumbar spine in the estimation of whole body composition, while the work of Cespedes et al [41] demonstrated the value of an automated approach in the study of cancer prognosis. Finally, Lee et al [42] used an advanced 3D Unet technique to provide an accurate and e cient method for body composition segmentation for whole-body PET-CT images.…”
Section: Progress In Body Composition Segmentation On Ct Imagesmentioning
confidence: 99%